Interaction Diversity Maintains Resiliency in a Frequently Disturbed Ecosystem - Dell, Jane E.; Salcido, Danielle M.; Lumpkin, Will; Richards, Lora A.; Pokswinski, Scott M.; Loudermilk, E. Louise; O'Brien, Joseph J.; Dyer, Lee A. (Frontiers in Ecology and Evolution, 2019)
Frequently disturbed ecosystems are characterized by resilience to ecological disturbances. Longleaf pine ecosystems are not only resilient to frequent fire disturbance, but this feature sustains biodiversity. We examined how fire frequency maintains beta diversity of multi-trophic interactions in longleaf pine ecosystems, as this community property provides a measure of functional redundancy of an ecosystem. We found that beta interaction diversity at small local scales is highest in the most frequently burned stands, conferring immediate resiliency to disturbance by fire. Interactions become more specialized and less resilient as fire frequency decreases. Local scale patterns of interaction diversity contribute to broader scale patterns and confer long-term ecosystem resiliency. Such natural disturbances are likely to be important for maintaining regional diversity of interactions for a broad range of ecosystems.